Group 2 innate lymphoid cells boost CD8+ T-cell activation in anti-tumor immune responses - Jing Wen; Shipeng Cheng; Ran Wang; Yuying Huang; Long Xu; Liyan Ma; Zhiyang Ling; Jinfu Xu; Deping Zhao; Yaguang Zhang; Bing Sun (OncoImmunology)
Group 2 innate lymphoid cells (ILC2s) are essential for orchestrating type 2 immune responses during allergic airway inflammation and infection. ILC2s have been reported to play a regulatory role in tumors; however, this conclusion is controversial. In this study, we showed that IL-33-activated ILC2s could boost CD8+ T-cell function through direct antigen cross-presentation. After activation by IL-33, ILC2s showed an enhanced potential to process antigens and prime CD8+ T cell activation. Activated ILC2s could phagocytose exogenous antigens in vivo and in vitro, promoting antigen-specific CD8+ T cell function to enhance antitumor immune responses. Administration of OVA-loaded ILC2s induces robust antitumor effects on the OVA-expressing tumor model. These findings suggested that the administration of tumor antigen-loaded ILC2s might serve as a potential strategy for cancer treatment.